2013
DOI: 10.1016/j.jhazmat.2013.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cuprous chloride and simultaneous recovery of Ag and Pd from waste printed circuit boards

Abstract: h i g h l i g h t s• An environmentally friendly process was developed for high quality cuprous chloride synthesis from waste PCBs.• Neither corrosive acid nor strong oxidant was used in the process.• Ag and Pd were simultaneously recovered during cuprous chloride synthesis.• A much faster reaction rate was achieved compared with other recovery methods.a r t i c l e i n f o t r a c tA benign and effective process for cuprous chloride synthesis and simultaneously recovery of Ag and Pd from waste printed circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…were disassembled when we received these materials. The PCBs were pretreated by thermal shock process [27] and crushed in a hammer crusher. Then, a centrifugal air separator was used to obtain the metallic components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…were disassembled when we received these materials. The PCBs were pretreated by thermal shock process [27] and crushed in a hammer crusher. Then, a centrifugal air separator was used to obtain the metallic components.…”
Section: Methodsmentioning
confidence: 99%
“…Palladium was enriched during copper recovery process according to our previous study [27,28] with minor modification. The flow chart of the whole process was shown in Fig.…”
Section: Enrichment and Dissolution Of Palladiummentioning
confidence: 99%
“…and then their product precipitated in the PMC. Oxidation and complexation reactions between Cu 2+ and Pd/Ag were shown as follows [29]:…”
Section: Optimization Of the Extraction Parametersmentioning
confidence: 99%
“…Very few researches have been carried out on the enrichment characteristics of precious metals under supercritical conditions. Our previous studies revealed that dispersal precious metals in electronic waste could be enriched by a non-acid process and extracted by solvent methods [28,29]. However, the treatment of waste liquors after the solvent extraction process is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have done a lot of research and mainly focus on the extraction of valuable metals like Au, Ag and Cu from various kinds of e-wastes (Hagelüken, 2006;Park and Fray, 2009;Zhang and Zhang, 2013). Although the heavy metal contamination has been reported a lot, the recycling of heavy metals like Pb, Cd and Zn in e-wastes has not attracted enough attention because of their nominal prices.…”
Section: Introductionmentioning
confidence: 99%